Reformasi Pendidikan Islam di Semenanjung Melayu: Studi Perbandingan Karakteristik Sistem Pondok Tradisional dan Madrasah Abad Ke 20 - Khaerotun Nisa; Raida Sulistiya; Saif ‘Abdul Fatah (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
This article examines the transformation of Islamic education in the Malay Peninsula through a comparative analysis of traditional pondok systems and 20th-century madrasah. Employing a qualitative approach with descriptive- analytical design and comparative method, the study reconstructs historical dynamics through literature review. Findings indicate that this educational shift was driven by five interrelated factors: state educational policies, socio- cultural changes, demands for modernity and standardization, economic dynamics, and initiatives from ulama and Islamic organizations. Characteristically, traditional pondoks relied on centralized kiai authority, classical text- based curricula, and personalized sorogan and bandongan methods. In contrast, the 20th-century madrasah adopted formal administration, integrated religious and general curricula, classical classroom instruction, and specialized teaching roles. The reform generated educational dualism, fostered nationalist consciousness, shifted reasoning from taqlid to ijtihad, and expanded learning opportunities for women. Essentially, this transformation reflects an adaptive strategy through which Malay Muslims engaged modernity while preserving traditional scholarly heritage, laying the intellectual groundwork for contemporary Islamic education in the region. Keywords: 20th-century madrasah, Islamic education, Traditional Pondok, Educational Reform, Malay